2017
DOI: 10.14257/ijunesst.2017.10.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Entrepreneurship into Engineering Education

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…A feasible strategy is to integrate and implement entrepreneurship skills into technical colleges' curricula. This idea is supported by researchers like [1] who conducted a study and reported that entrepreneurship skills should be embedded in curricula across all educational level and types so as to enhance socio-economic development of individuals and nations. Figure 1 shows an illustration of six countries studied, where entrepreneurship skills integration into school based curricula were conducted and reported in the work of [2].…”
Section: Introductionmentioning
confidence: 94%
“…A feasible strategy is to integrate and implement entrepreneurship skills into technical colleges' curricula. This idea is supported by researchers like [1] who conducted a study and reported that entrepreneurship skills should be embedded in curricula across all educational level and types so as to enhance socio-economic development of individuals and nations. Figure 1 shows an illustration of six countries studied, where entrepreneurship skills integration into school based curricula were conducted and reported in the work of [2].…”
Section: Introductionmentioning
confidence: 94%
“…Some examples include: a. Entrepreneurship Programs and Courses [4], [9], [10] jects into engineering curricula allows students to apply their technical knowledge to real-world problems, encouraging an entrepreneurial mindset and promoting collaboration with industry partners. By incorporating these practices and models, engineering departments/institutions can create a comprehensive ecosystem that nurtures an entrepreneurial culture, prepares students for entrepreneurial endeavours, and fosters innovation and economic growth.…”
Section: Practices and Models For Integrating Entrepreneurship Into E...mentioning
confidence: 99%
“…Introducing a general framework for integrating entrepreneurship studies into different engineering curricula, which is motivated by the need to develop the economy, was introduced in [36]. This study argues that EE should provide more than the basic technical skills to help engineers become successful freelancers who can provide high-quality services in diverse domains.…”
Section: An Active Learning Approach For Applying Steamed-based Educa...mentioning
confidence: 99%